1990
DOI: 10.1002/bjs.1800770822
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating visceral injuries of the neck: Results of a conservative management policy

Abstract: A study of the conservative treatment of 109 patients with penetrating neck injuries was carried out over 3 years. Patients with clinical or radiological evidence of injury to the oesophagus or trachea were included in the study while nine patients with major vascular trauma were explored immediately and excluded. Three late vascular operations were performed. The remaining 106 patients were treated conservatively. There were two deaths, both from associated injuries. The remaining 104 patients were treated su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 17 publications
5
31
1
Order By: Relevance
“…These 28 patients constituted 13% of patients with odynophagia associated with neck injuries. These findings are in keeping with those of Ngakane et al,9 where only 14% of patients with odynophagia were shown to have cervical oesophageal injury. Both these studies confirm that odynophagia alone is not pathognomonic of cervical oesophageal injury.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These 28 patients constituted 13% of patients with odynophagia associated with neck injuries. These findings are in keeping with those of Ngakane et al,9 where only 14% of patients with odynophagia were shown to have cervical oesophageal injury. Both these studies confirm that odynophagia alone is not pathognomonic of cervical oesophageal injury.…”
Section: Discussionsupporting
confidence: 92%
“…[9][10][11] Oesophageal injuries occurred in 2% of neck injuries in this series. There was an average of 4-5 oesophageal injuries per year, which falls within the rate of 2-9 cases per year reported by most busy trauma centres.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Nonetheless, conservative measures were successfully used in 4 patients with ruptures ranging in length between 1 and 4 centimetres (cases 19, 20, 21 and 23). Such experience, even if limited to four cases, couples with previously reported series in suggesting that the conservative treatment plays a role in traumatic disruptions [20][21][22][23][24][25][26].…”
Section: Discussionsupporting
confidence: 59%
“…Nonetheless, a few cases and a few recent series have been reported with even wide full-thickness iatrogenic tracheal lacerations successfully managed by means of conservative treatment [10][11][12][13][14][15][16][17]. As far as traumatic ruptures are concerned, surgical treatment is advocated in most cases as well [18][19], but the conservative treatment has been reported also [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%